Is testicular microdissection the only way to retrieve sperm for non-obstructive azoospermic men? - Vieira, Marcelo; Bispo de Andrade, Marcos Alécio; Santana-Santos, Eduesley (Frontiers in Reproductive Health, 2022)
Men presenting with non-obstructive azoospermia are the most challenging clinical scenario for an infertile couple. Intracytoplasmic Sperm Injection (ICSI) with testicular sperm retrieval gave a chance for biological fatherhood once sperm can be found, but unfortunately sperm recovery rate (SSR) is something near 50%, leading to a discussion about what surgical retrieval technique is the best. Historically sperm have been retrieved using conventional Testicular Sperm Extraction (c-TESE), Testicular Sperm Aspiration (TESA), a combination of Testicular Fine Needle Aspiration (TfNA)/c-TESE, Testicular Microdissection (TM) and Open Testicular Mapping (OTEM). c-TESE published in 1995 by Devroey and cols. consists of testis delivery, a large unique albuginea incision and extraction of a portion from the majority of testicular tubules. TESA published in 1996 by Lewin and cols. is done percutaneously using a 21–23 gauge needle and a syringe to aspire testicular tubules. TfNA was published in 1965 by Obrant and Persson as an aspiration biopsy and cytological exam to verify sperm production. In 1999 Turek and cols. published the use of TfNA combined with c-TESE for sperm retrieval. In 1999, Peter Schlegel published a technique using a microsurgical approach to identify more probable sperm production areas inside the testicle that could be excised with better precision and less tissue. OTEM is a multiple biopsy approach, published in 2020 by Vieira and cols., based on TfNA principles but done at the same time without albuginea opening or surgical microscope need. Since Testicular Microdissection publication, the method became the gold standard for sperm retrieval, allowing superior SSR with minimal tissue removal, but the amount of testicular dissection to find more probable spermatogenesis areas, difficulties in comparative design studies, diversity TM results among doctors and other methods that can achieve very similar results we question TM superiority. The objective is review existing literature and discuss advantages and disadvantages of all the methods for sperm retrieval in non-obstructive azoospermia.